2006
DOI: 10.1007/s10439-006-9209-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Shear Properties of the Porcine Molar and Incisor Periodontal Ligament

Abstract: The role of the periodontal ligament (PDL) is to support the tooth during function and resist external forces applied to it. The dominant vertical component of these forces is associated with shear in the PDL. The mechanical response to vertical force may, however, be different between the molar and incisor as their loading regimen is different. The present study was designed to determine the viscoelastic behavior in shear of the PDL of the porcine molar and incisor (n = 10 for each). From dissected mandibles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Tanaka et al (2006) [79] have measured dynamic shear properties of the porcine incisor and molar PDLs at an oscillation amplitude (Figure 17) of Δ γ = 1% with a wide range of frequencies (0.01–100 Hz). They found that storage modulus G ′ increased with frequency for both PDLs while loss modulus G ′′ did so only for the incisor PDL (Figure 18(a)).…”
Section: Dynamic Measurements Of Viscoelastic Responses Of the Pdlmentioning
confidence: 99%
See 3 more Smart Citations
“…Tanaka et al (2006) [79] have measured dynamic shear properties of the porcine incisor and molar PDLs at an oscillation amplitude (Figure 17) of Δ γ = 1% with a wide range of frequencies (0.01–100 Hz). They found that storage modulus G ′ increased with frequency for both PDLs while loss modulus G ′′ did so only for the incisor PDL (Figure 18(a)).…”
Section: Dynamic Measurements Of Viscoelastic Responses Of the Pdlmentioning
confidence: 99%
“…Tan  δ ( = G ′′/ G ′) ranged between 0.1 and 0.2, which was greater in the incisor than in the molar PDL with frequencies between 1 and 100 Hz (Figure 18(b)). The incisor PDL may be considered to have better shock-absorbing characteristics for sudden loading [79]. …”
Section: Dynamic Measurements Of Viscoelastic Responses Of the Pdlmentioning
confidence: 99%
See 2 more Smart Citations
“…Early investigators isolated and performed biomechanical studies on transverse sectioned blocks of the bone-PDL-tooth complex and focused on the PDL’s intrusive, extrusive and related viscoelastic/viscoplastic characteristics [2226]. Subsequently, by using an in situ mechanical loading device coupled to an x-ray microscope, biomechanical studies on intact bone-PDL-tooth fibrous joints, and geometric relationship of tooth with the alveolar socket in humans [27] and other mammalian models under normal [2830] and diseased conditions [31] were performed.…”
Section: Introductionmentioning
confidence: 99%